Construction of Ni@Pt/N-doped nanoporous carbon, derived from pyrolysis of nickel metal organic framework, and application for HER in alkaline and acidic solutions. (10th December 2019) - Dehcheshmeh, Mohammad Mohammadi; Karimi Shervedani, Reza; Torabi, Mostafa
Abstract: Owing to the growing significance of hydrogen as a non-polluting fuel, design and construction of low-cost, efficient and highly stable electrocatalysts are required for its production by means of water electrolysis. Herein, a general strategy is introduced to fabricate a new type of electrocatalysts based on bimetallic core@shell structure formed on nitrogen-doped nanoporous carbon for electrocatalytic hydrogen evolution reaction (HER). Accordingly, a nickel metal organic framework, Ni‒MOF, synthesized by using benzene-1, 3, 5-tricarboxylic acid (H3 BTC) as the carbon source and 2-methyl-imidazole as the carbon and nitrogen source, is employed, and the nickel/nitrogen−doped nanoporous carbon composite, Ni/NNPC system, is synthesized by the direct carbonization of Ni‒MOF system, i.e. annealing the system in argon atmosphere without using any carbon precursor additive. Then, the outer layers of nickel in Ni/NNPC system are replaced by Pt via galvanic reaction to synthesize the nanostructured system, Ni metal core@Pt thin layer shell, Ni@Pt/NNPC. The step-by-step synthesis of the system and formation of core@shell was supported by several surface analysis techniques. The fabricated materials were transferred onto a glassy carbon (GC) electrode and studied for the HER. The electrochemical results revealed a large electrocatalytic activity for the GCE/Ni@Pt/NNPC system toward the HER in both alkaline and acidic media, compared with GCE, GCE/Ni−MOF and GCE/Ni/NNPC. Tafel slopes of 43.78 and 46.73 mV dec −1, and overpotentials of −33.80 and −76.32 mV (vs RHE) at 20 mA cm −2 (η20 ) were observed on GCE/Ni@Pt/NNPC electrode in the alkaline and acidic media, under the same conditions, respectively. The observed activity is attributed to (i) the increased electrochemically active surface area, (ii) the cooperative action or synergistic effect between the Pt thin layer shell and the Ni metal core as well as between the Ni@Pt nanoparticles and the NNPC platform, and (iii) effective pore structures of the Ni@Pt/NNPC system. Graphical abstract: Image 1 Highlights: Nickel/nitrogen-doped nanoporous carbon (Ni/NNPC) fabricated by the carbonization of Ni-MOF. The Ni(core)@Pt(shell) structures formed on Ni/NNPC via galvanic replacement of Ni by Pt. Based on the ICP analysis, the amount of Pt in the system was 7%, compared with 20% in Pt/C. The system exposed excellent electrocatalytic activity for HER in both acidic and alkaline media. The activities originate from synergistic effects, improved EASA, and pore structures.